Photosynthetic performance and antioxidant activity of Gracilariopsis lemaneiformis are sensitive to phosphorus deficiency in elevated temperatures - Zhang, Di; Sun, Jia-Zhen; Fu, Ming-Hui; Li, Chang-Jun (Frontiers in Marine Science, 2024)
Due to anthropogenic input of nutrients and emissions of greenhouse gases, macroalgae inhabiting coastal areas often experience drastic fluctuations in nutrients and seawater warming. In this work, we investigated the photosynthetic performance and antioxidant response of the commercially important red macroalgae Gracilariopsis lemaneiformis under four different nutrient conditions at 20°C and 23°C. Our results showed that the enrichment of NO3- and PO43- (high concentrations of nitrogen (N) and phosphorus (P), denoted as HNHP) significantly enhanced photosynthesis and growth by up to 42% and 66% for net photosynthesis rate and 83% and 134% for relative growth rate (RGR) under 20°C and 23°C, respectively, compared with natural seawater (low concentrations of N and P, denoted as LNLP). However, enriching only with PO43- (low concentration of N and high concentration of P, denoted as LNHP) or NO3- (high concentration of N and low concentration of P, denoted as HNLP) brought no significant change in RGR. A two-way ANOVA analysis revealed an interaction between nutrient variations and temperature, with elevated temperature intensifying the inhibition observed under HNLP conditions. To further elucidate this interaction, we assessed the damage and recovery processes of the photosynthetic apparatus, along with the antioxidant activities. The increased damage (k) and reduced recovery (r) rates of photosystem II (PSII) in both LNLP and HNLP conditions indicated a heightened susceptibility to photoinhibition in G. lemaneiformis, leading to reactive oxygen species (ROS) accumulation and exacerbated oxidative stress, culminating in decreased photosynthesis and growth rates. At higher temperatures, these phosphorus deficiency-induced inhibitions were amplified, as evidenced by increases in k values and ROS contents, coupled with a decrease in r values. In summary, our data suggest that the photosynthetic performance and growth of G. lemaneiformis are vulnerable to phosphorus deficiency, particularly in the context of future ocean warming. Consequently, phosphorus fertilization during cultivation warrants more attention.